Afrodescendancy and Territory. Afro-rural identities and agrarian conflicts in the Azapa Valley (Chile) - Araya Morales, Isabel (2023)
This article analyzes the link between territory and Afro-descendant identity in the Azapa Valley. Since 2000, an Afro-Chilean movement has emerged to demand state recognition. Within it, a particular group claims the valley as its own territory, which shows changes as a result of the introduction of agroindustries and seed companies. At the methodological level, between 2012 and 2014, an ethnographic study was conducted on the history of black populations and their link with the valley. It is concluded that the emergence of an "Afro- Azapeño" identity is presented as one of the resources that mobilizes collective actions for territorial defense.